2013
DOI: 10.3389/fpsyg.2013.00852
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the validity of the virtual spatial navigation assessment

Abstract: This correlational study investigated a new measure of environmental spatial ability (i.e., large scale spatial ability) called the virtual spatial navigation assessment (VSNA). In the VSNA, participants must find a set of gems in a virtual 3D environment using a first person avatar on a computer. The VSNA runs in a web browser and automatically collects the time taken to find each gem. The time taken to collect gems in the VSNA was significantly correlated to three other spatial ability measures, math standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
6
37
1
Order By: Relevance
“…The improvement of subjects on their spatial skills as a function of playing Portal 2 is likely due to the repeated requirement in Portal 2 to apply and practice their spatial skills to solve problems. This result supports other work investigating video game use and spatial skill (e.g., Feng et al, 2007 ;Uttal et al, 2012 ;Ventura et al, 2013 ). There were no improvements for the Lumosity group on any of the three spatial tests.…”
Section: Results From a Controlled Evaluation Of Portalsupporting
confidence: 88%
See 1 more Smart Citation
“…The improvement of subjects on their spatial skills as a function of playing Portal 2 is likely due to the repeated requirement in Portal 2 to apply and practice their spatial skills to solve problems. This result supports other work investigating video game use and spatial skill (e.g., Feng et al, 2007 ;Uttal et al, 2012 ;Ventura et al, 2013 ). There were no improvements for the Lumosity group on any of the three spatial tests.…”
Section: Results From a Controlled Evaluation Of Portalsupporting
confidence: 88%
“…Over the past 20 years, a growing body of research has shown that playing action video games can improve performance on tests of spatial cognition and selective attention (e.g., Dorval & Pepin, 1986 ;Feng, Spence, & Pratt, 2007 ;Green & Bavelier, 2003, Spence, Yu, Feng, & Marshman, 2009Uttal et al, 2012 ). Recently, Ventura, Shute, Wright, and Zhao ( 2013 ) showed that self-reported ratings of video game use were signifi cantly related to all three facets of spatial cognition, and most highly related to environmental spatial skill. Feng et al ( 2007 ) found that playing an action video game improved performance on a mental rotation task (i.e., small-scale or fi gural spatial cognition).…”
Section: Spatial Skillsmentioning
confidence: 99%
“…The Santa Barbara Sense of Direction (SBSOD) (Hegarty et al., ) is a standard questionnaire consisting of fifteen items on sense of direction in a large‐scale environment. Example items are “I very easily get lost in a new city” and “I can usually remember a new route after I have travelled it only once.” Participants were instructed to indicate the extent to which they agreed or disagreed with each statement in a 5‐point Likert‐type scale (Hund & Nazarczuk, ; Ventura, Shute, Wright, & Zhao, ). The total SBSOD score was used to index the participants’ sense of direction, with higher scores indicating better navigation ability.…”
Section: Methodsmentioning
confidence: 99%
“…In this type of assessment, participants are asked to find objects in a virtual 3D environment (Ventura et al, 2013). The time taken to fulfill this task is regarded as an indication of participants’ spatial ability.…”
Section: Multidimensional Linguistic Cues Frameworkmentioning
confidence: 99%